A stagflation-proof bill of exchange circulation model – Presentation and evaluation - Novák, Zsuzsanna; Szalay, Zsuzsanna (Public Finance Quarterly, 2023)
As a continuation of a preceding article discussing liquidity creation based on promissory notes and bills of exchange, the present study introduces how the use of notes and bills can foster the particular economic sectors and public debt management at a time. A financial policy package of measures first suggested by Lautenbach then introduced by Schacht fought off recession and inflation within half a decade in the German economy. We make up for a professional hiatus in the Hungarian economic literature, in that we provide a detailed evaluation of the financial solution of Schacht which has appeared in many forms in the international literature.. The then used economic model is worth considering under current economic conditions, especially if combined with Fintech methods. Suggestions for potential applications taking into consideration stagflation and endogenous growth are the following: they (1) can stop and turn recession to growth, (2) do not require external financing, (3) mitigate the burden of public debt financing, (4) have an inflation moderating effect, (5) are worth implementing in, among others, sectors such as energy, environmental protection, agriculture, wholesale and retail trade, social protection.